Kurikulum pendidikan politik dan relevansinya dalam meningkatkan kesadaran politik peserta didik di Indonesia - Pelas, Mina Umrah; Hutabarat, Putra Kaslin; Maulina, Maulina; Jauhari, Winalda Makhrivikia; Warahmah, Sarmila; Murtada, Rifaldi (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
The political education curriculum plays a crucial role in fostering political awareness and participation among young generations from an early age. This study aims to analyze the role of the political education curriculum in enhancing students’ political awareness and participation in schools, identify the challenges in its implementation in Indonesia, and offer solutions to improve its effectiveness. Using a qualitative approach through library research, the study finds that a curriculum integrated with democratic values, civic participation, and contextual learning can positively encourage students’ involvement in political life. However, challenges such as teachers’ limited competencies, inadequate teaching materials, and cultural resistance hinder its optimal implementation. As a solution, strengthening teacher capacity, updating curriculum content to reflect current socio-political dynamics, and promoting collaboration between schools, government, and civil society organizations are necessary. Therefore, the political education curriculum in schools, when implemented effectively, can function as a strategic tool to foster a democratic, participative, and critical generation of citizens.